Host gene expression analysis in Sri Lankan melioidosis patients. - Shivankari Krishnananthasivam; Nimanthi Jayathilaka; Harindra Darshana Sathkumara; Enoka Corea; Mohan Natesan; Aruna Dharshan De Silva (Public Library of Science (PLoS), 2017)
Melioidosis is a life threatening infectious disease caused by the gram-negative bacillus Burkholderia pseudomallei predominantly found in southeast Asia and northern Australia. Studying the host transcription profiles in response to infection is crucial for understanding disease pathogenesis and correlates of disease severity, which may help improve therapeutic intervention and survival. The aim of this study was to analyze gene expression levels of human host factors in melioidosis patients and establish useful correlation with disease biomarkers, compared to healthy individuals and patients with sepsis caused by other pathogens.The study population consisted of 30 melioidosis cases, 10 healthy controls and 10 sepsis cases caused by other pathogens. Total RNA was extracted from peripheral blood mononuclear cells (PBMC's) of study subjects. Gene expression profiles of 25 gene targets including 19 immune response genes and 6 epigenetic factors were analyzed by real time quantitative polymerase chain reaction (RT-qPCR).Inflammatory response genes; TLR4, late onset inflammatory mediator HMGB1, genes associated with antigen presentation; MICB, PSMB2, PSMB8, PSME2, epigenetic regulators; DNMT3B, HDAC1, HDAC2 were significantly down regulated, whereas the anti-inflammatory gene; IL4 was up regulated in melioidosis patients compared to sepsis cases caused by other pathogens. Septicaemic melioidosis cases showed significant down regulation of IL8 compared to sepsis cases caused by other pathogens. HMGB1, MICB, PSMB8, PSMB2, PSME2, HDAC1, HDAC2 and DNMT3B showed consistent down regulation of gene expression in melioidosis patients compared to other sepsis infection, irrespective of comorbidities such as diabetes, duration of clinical symptoms and antibiotic treatment.Specific immune response genes and epigenetic regulators are differentially expressed among melioidosis patients and patients with sepsis caused by other pathogens. Therefore, these genes may serve as biomarkers for disease diagnosis to distinguish melioidosis from cases of sepsis due to other infections and therapeutic intervention for melioidosis.